MITIGATING CONSTRUCTION DELAYS USING MONTE CARLO SIMULATION: A RISK BASED APPROACH - Fadilla, Meutia (Center for Study and Journal Management FTI UMI, 2025)
This study analyzes the schedule delays in the foundation work of an ammonia tank construction project at a fertilizer company in Sumatra. The research identifies key risks affecting the project's schedule and assesses their impact using Monte Carlo simulation. A risk analysis framework is developed by integrating deterministic scheduling with uncertainty modeling to quantify the probability of project completion within the planned timeframe. The study applies a two-stage risk analysis approach, consisting of pre-mitigation and post-mitigation assessments. The pre-mitigation analysis shows a low probability (22%) of completing the project on time due to high-impact risks such as material delivery delays and equipment failures. Based on these findings, mitigation strategies were implemented, including optimized procurement scheduling, quality control measures, and enhanced equipment maintenance. The post-mitigation simulation results indicate a significant improvement, increasing the probability of on-time project completion to 43%. This research highlights the effectiveness of Monte Carlo simulation in identifying critical risks, optimizing mitigation measures, and improving project schedule reliability.